2017
DOI: 10.1093/femsyr/fox010
|View full text |Cite
|
Sign up to set email alerts
|

Selection of non-Saccharomyces yeasts to be used in grape musts with high alcoholic potential: a strategy to obtain wines with reduced ethanol content

Abstract: Ethanol content of wine has increased over the last decades as consequence of searching phenolic maturity, requiring increased grape maturity. This may result in the production of wines with excessive alcohol levels (sometimes more than 15% (v/v)), sluggish and stuck fermentations and excessive volatile acidity. Many strategies to reduce ethanol in wines are being studied, and microbial methods have some additional advantages. However, because of the broad intra- and interspecies variability, new selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 57 publications
6
49
0
Order By: Relevance
“…In this study, all isolates of M. pulcherrima were able to grow under the maximum level of H 2 O 2 tested (Figure 2 and Table S1). Our results are consistent with those found by Furlani et al [16] that evaluated H 2 O 2 tolerance in this and other non-Saccharomyces species. The authors suggested that this feature could be associated with the catalase activity expressed by these yeasts.…”
Section: Phenotypic Characterizationsupporting
confidence: 94%
“…In this study, all isolates of M. pulcherrima were able to grow under the maximum level of H 2 O 2 tested (Figure 2 and Table S1). Our results are consistent with those found by Furlani et al [16] that evaluated H 2 O 2 tolerance in this and other non-Saccharomyces species. The authors suggested that this feature could be associated with the catalase activity expressed by these yeasts.…”
Section: Phenotypic Characterizationsupporting
confidence: 94%
“…It is well known that H. uvarum is the most representative yeast species found on grape surfaces showing prevalence during early stages of spontaneous alcoholic fermentation [32]. This yeast has several characteristics that could be used to reduce ethanol content in wines [21]. In the current study, inoculation of H. uvarum BHu9 prior to inoculation of S. cerevisiae BSc114 demonstrated a sugar consumption of 35.7 g/L for 1% of ethanol produced.…”
Section: Discussionmentioning
confidence: 56%
“…In addition to the aforementioned effects, this yeast group is also known to be less efficient in the production of ethanol from consumed sugars when compared with S. cerevisiae yeasts [19].Hanseniaspora genera as a whole and particularly Hanseniaspora uvarum species are non-Saccharomyces yeasts commonly encountered at high concentrations on the grape surface and throughout the fermentation process [20]. Recently, 28 H. uvarum isolates were evaluated by our research group and they demonstrated interesting enological characteristics such us: ability to grow at high sugar, ethanol and SO 2 contents; to produce high concentrations of glycerol; low acetic acid and hydrogen sulfide levels; and the release of proteolytic enzymes [21]. Moreover, it is important to highlight that H. uvarum was also found to be a potential candidate to produce less ethanol because it requires more than 19 g/L of consumed sugar to produce 1% v/v of ethanol [21].…”
mentioning
confidence: 99%
See 2 more Smart Citations